A Supramolecular Polymer Network of Graphene Quantum Dots. Issue 18 (23rd March 2018) - Uemura, Yuichiro; Yamato, Kairi; Sekiya, Ryo; Haino, Takeharu
Abstract: Graphene quantum dot (GQD)–organic hybrid compounds (GQD‐2 b –e ) were prepared by introducing 3, 4, 5‐tri(hexadecyloxy)benzyl groups (C16) and linear chains terminated with a 2‐ureido‐4‐[1H]‐pyrimidinone (UPy) moiety onto the periphery of GQD‐1 . GQD‐2 b –e formed supramolecular assemblies through hydrogen bonding between the UPy units. GPC analysis showed that GQDs with high loadings of the UPy group formed larger assemblies, and this trend was confirmed by DOSY and viscosity measurements. AFM images showed the polymeric network structures of GQD‐2 e on mica with flat structures (ca. 1.1 nm in height), but no such structures were observed in GQD‐2 a, which only carries the C16 group. GQD‐2 c and GQD‐2 d formed organogels in n ‐decanol, and the gelation properties can be altered by replacing the alkyl chains in the UPy group with ethylene glycol chains (GQD‐3 ). GQD can thus be used as a platform for supramolecular polymers and organogelators by suitable chemical functionalization. Abstract : Molecular filo pastry : A graphene quantum dot (GQD)–organic hybrid supramolecular polymer network is realized by the introduction of the hydrogen‐bonding functional groups into edge‐functionalized GQDs through click chemistry. The interactions between GQDs led to supramolecular assemblies, which in turn lead to polymeric assemblies.